Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1177/026988110101500209
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and schizophrenia

Abstract: Suicide and suicide attempts occur at a significantly greater rate in schizophrenia than in the general population. Common estimates are that 10% of people with schizophrenia will eventually have a completed suicide, and that attempts are made at two to five times that rate. Demographically associated with suicidality in schizophrenia are being young, being early in the course of the illness, being male, coming from a high socioeconomic family background, having high intelligence, having high expectations, not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
156
4
21

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(193 citation statements)
references
References 133 publications
12
156
4
21
Order By: Relevance
“…Hopelessness, substance abuse, greater insight into illness, and higher cognitive function are associated with greater risk for suicidal behavior in chronic schizophrenia, with hopelessness being the principal predictor (Kim et al, 2003). A recent review also found that the most common correlates of suicidality in schizophrenia are depressive symptoms and the depressive syndrome, although severe psychotic and panic-like symptoms may contribute as well (Siris, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Hopelessness, substance abuse, greater insight into illness, and higher cognitive function are associated with greater risk for suicidal behavior in chronic schizophrenia, with hopelessness being the principal predictor (Kim et al, 2003). A recent review also found that the most common correlates of suicidality in schizophrenia are depressive symptoms and the depressive syndrome, although severe psychotic and panic-like symptoms may contribute as well (Siris, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Although concurrent depressive symptoms were previously considered a good prognostic indicator (Stephens et al, 1966), research that is more recent has demonstrated that depressive symptoms serve as a poor prognostic indicator of recovery and reintegration into the community (Resnick et al, 2004). Depressive symptoms worsen quality of life (Reine et al, 2003) and increase the risk of suicide (Siris, 2001), psychotic relapse, and psychiatric hospitalization (Tollefson et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of depressive symptoms among people with schizophrenia has been reported to range from 25% to 81% (Siris, 2001), depending on the treatment setting, phase of the illness, and the definition of depression. It is currently unclear what proportion of people with schizophrenia treated in usual practice settings experience at least a moderate level of depressive symptoms, whether the rates of depressive symptoms change over time, or which specific functional outcomes are more adversely affected by depressive symptoms during the course of the illness.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study raise the possibility that perceptions of defeat and entrapment could be used alongside better established indicators of suicide such as depression and hopelessness 200,230,[250][251][252][253] to identify patients diagnosed with schizophrenia who are at heightened risk of suicide. Further investigation of the utility of defeat and entrapment in predicting suicidal behaviour is therefore warranted.…”
Section: Discussionmentioning
confidence: 99%